Transforming Indonesian language learning evaluation through OBE: A multisite mixed-methods study of speaking assessment in higher education - Muhlis Fajar Wicaksana; Nurratri Kurnia Sari; Dewi Kusumaningsih; Nanci Risky Rimadani; Ly Aminas (Universitas Muhammadiyah Malang, 2025)
Evaluation of Indonesian language learning in an Outcome-Based Education (OBE) context requires more than grading or collecting digital assignments; it requires traceable alignment among learning outcomes, tasks, criteria, evidence, feedback, and improvement. This convergent multisite mixed-methods needs-assessment study investigated the transformation of speaking evaluation across seven higher-education institutions in Central Java. Participants comprised 10 lecturers of Speaking Skills courses in Indonesian Language and Literature Education programs, and 132 students, from whom 140 questionnaires were distributed; eight incomplete responses were excluded. Data were collected through semi-structured interviews, reviews of course plans, rubrics, speaking tasks, and digital evidence, and a ten-item Likert questionnaire. The questionnaire was content-validated by three experts and piloted with 30 students. Quantitative data were summarized using frequencies, means, standard deviations, and positive-response percentages, while qualitative evidence was examined through cross-site thematic comparison and integrated in a joint display. The overall questionnaire mean was 3.93/5. Rubric clarity received the highest mean (M = 4.10), and the importance of OBE-aligned technology-based evaluation received the strongest positive response (77.27%; M = 4.09). Experience using digital platforms for speaking-task submission was lowest (61.36%; M = 3.75). Lecturer and document evidence showed that authentic tasks, linguistic and nonlinguistic criteria, and OBE terminology were present, but digital tools remained concentrated on communication, submission, publication, and storage. Outcome mapping, rater calibration, timely feedback, longitudinal evidence, analytics, and ethical governance were not yet systematic. The study formulates a six-stage framework for transforming Indonesian language speaking evaluation through OBE: outcome alignment, authentic tasks, analytic rubrics, digital evidence, feedback and reflection, and outcome analytics for continuous improvement. The framework is a design proposition requiring validation and field testing.